Relationship between fecal calprotectin level and disease activity in patients with hidradenitis suppurativa - Eser, Emel; Engin, Burhan; Yuksel, PELİN; YÜKSEL MAYDA, PELİN; Kocazeybek, Bekir Sami; Kutlubay, Zekayi; Serdaroglu, Server; Askin, Ozge (My University, 2020)
Background Hidradenitis suppurativa is a chronic, inflammatory, recurrent disease with recurrent abscesses, and sinus tract formation leading to scarring. Calprotectin has immunomodulatory, antimicrobial, and antiproliferative properties and is a calcium-binding protein primarily found in the neutrophil cytoplasm. In recent years, a significant relationship between the activity of various diseases and the level of calprotectin has led to the conclusion that there may be a similar relationship in hidradenitis suppurativa.